Sugars and fats - C Schuh, Mari (Mankato, Minn Capstone Press, 2013)
Simple text and photos describe USDA's MyPlate tool and healthy sugar and fat choices for children"--Provided by publisher. Includes notes to parents and teachers. Suggested level: junior, primary
World around us (Human body)
1 2 13 15
Keywords: Confectionery -- Juvenile literature; Oils and fats -- Juvenile literature; Sugars in human nutrition -- Juvenile literature